2014
DOI: 10.3109/17435390.2014.907456
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-functionalized and amino-functionalized multiwall carbon nanotubes on pesticide uptake by lettuce (Lactuca sativaL.)

Abstract: The effect of non-functionalized and amino-functionalized multiwall carbon nanotube (CNT) exposure, as well as the impact of CNT presence on coexistent pesticide accumulation, was investigated in lettuce (Lactuca sativa L.). Lettuce seeds were sown directly into CNT-amended vermiculite (1000 mg L(-1)) to monitor phytotoxicity during germination and growth. During growth, lettuce seedlings were subsequently exposed to chlordane (cis-chlordane [CS], trans-chlordane [TC] and trans-nonachlor [TN]) and p,p'-DDE (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 52 publications
(60 reference statements)
2
30
0
Order By: Relevance
“…However, little is known about the effect of SPAOMs on CNTs fate in planted systems. There are limited but related studies focusing on accumulation of pesticides by plants in the presence of CNTs [33][34][35]. The results showed that pesticide uptake was generally reduced by CNTs [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the effect of SPAOMs on CNTs fate in planted systems. There are limited but related studies focusing on accumulation of pesticides by plants in the presence of CNTs [33][34][35]. The results showed that pesticide uptake was generally reduced by CNTs [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…With plants, De La Torre‐Roche et al reported that coexposure to NP, bulk, or ionic Ag reduced the accumulation of freshly added DDE, although the magnitude of the effect was dependent on plant species as well as Ag type and concentration. Similarly, a 78% to 88% reduction in the accumulation of freshly added chlordane and DDE by lettuce ( Lactuca sativa L.) was reported on exposure to functionalized and bare carbon nanotubes . Conversely, De La Torre‐Roche et al reported that exposure to carbon nanomaterials could either increase or decrease pesticide uptake, depending on both the nanomaterial and the plant species.…”
Section: Resultsmentioning
confidence: 93%
“…Of specific concern are agricultural soils that receive or have received long‐term amendments in the form of organic chemicals (pesticides) and elements, including some heavy metals (pesticides, biosolids). Given the high surface area and reactivity of nanomaterials, the potential for cocontaminant interactions is high and could be complicated, with concerns ranging from food safety (increased pesticide/contaminant accumulation in the presence of nanomaterial) to food security (reduced yield from loss of pesticide/fertilizer efficacy or activity) . For example, accumulation of the solvent trichloroethylene by Populus deltoides (cottonwood) was increased by 82% on coexposure to C 60 fullerenes under hydroponic growth .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hamdi et al [111] found no effect of MWCNTs functionalized and non-functionalized on seed germination of lettuce (Lactuca sativa). Lin and Xing [112] evidenced no effect of MWCNTs on seed germination and root length of several plants (radish, rape, ryegrass, lettuce, corn, and cucumber) like Larue et al [20] in wheat and rapeseed.…”
Section: Fate and Impacts Of Carbon Nanotubes On Plantsmentioning
confidence: 99%